A critical discourse analysis of women’s portrayal in news reporting of sexual violence - Risdaneva Risdaneva (Universitas Syiah Kuala, 2018)
This study explores and compares the portrayal of women in the news reporting of crimes of sexual violence against women between two newspapers from different cultures, the Jakarta Post and the Guardian. The Jakarta Post is an English quality newspaper published in Indonesia, and the Guardian is a quality broadsheet from Great Britain. To explore the representation of women, this study accounts the portrayal of men as well since the two entities are strongly inter-related. The analytical tool used in this study is naming analysis of social actors, which is a part of critical discourse analysis. This analysis is aimed at probing the representation through the choice of lexical items in representing the main news actors. The findings of the analysis indicate that the choices of the naming categories used by both newspapers are different. The Jakarta Post mostly functionalises both the victims and the perpetrators in terms of their legal status in the criminal cases. This suggests that the broadsheet tends to view them as part of the legal processes instead of as people. The Guardian typically classifies the victims in terms of their age and gender and refers to the perpetrators with their surnames instead of as parts of the criminal cases. The Guardian’s tendency to represent both perpetrators and victims as people instead of parts of legal processes indicates that the paper is attempting to focus the reports more on the crimes themselves rather than the participants involved in the cases.